2020
DOI: 10.3390/diagnostics10050269
|View full text |Cite
|
Sign up to set email alerts
|

Male Breast Cancer: Results of the Application of Multigene Panel Testing to an Italian Cohort of Patients

Abstract: Male breast cancer (MBC) is a rare tumor, accounting for less than 1% of all breast cancers. In MBC, genetic predisposition plays an important role; however, only a few studies have investigated in depth the role of genes other than BRCA1 and BRCA2. We performed a Next-Generation Sequencing (NGS) analysis with a panel of 94 cancer predisposition genes on germline DNA from an Italian case series of 70 patients with MBC. Moreover, we searched for large deletions/duplications of BRCA1/2 genes through the Multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 109 publications
(126 reference statements)
0
25
0
Order By: Relevance
“…Studies that applied MGPT in cohorts of MBC found PVs in new genes of lower frequency in addition to those previously described [ 25 , 92 , 97 , 120 ]. Most studies applied gene panels containing between a dozen to a hundred of cancer predisposing genes, including some with unknown association with MBC ( Table 2 ).…”
Section: Inherited Pathogenic Variants Contribution To Mbc Developmentmentioning
confidence: 76%
See 2 more Smart Citations
“…Studies that applied MGPT in cohorts of MBC found PVs in new genes of lower frequency in addition to those previously described [ 25 , 92 , 97 , 120 ]. Most studies applied gene panels containing between a dozen to a hundred of cancer predisposing genes, including some with unknown association with MBC ( Table 2 ).…”
Section: Inherited Pathogenic Variants Contribution To Mbc Developmentmentioning
confidence: 76%
“…The estimated lifetime risk of BC is 5–10% among male BRCA2 PV carriers, compared to a 0.1% risk in the general population [ 85 , 86 , 87 ]. Germline PVs frequencies in the BRCA2 gene in MBC cohorts vary from 3.7% to 40%, depending on the characteristics of the studied population and their ancestral background [ 13 , 79 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. As it has been shown in FBC, the MBC phenotype is peculiar in men harboring BRCA1 / 2 PVs ( Table 1 ).…”
Section: Inherited Pathogenic Variants Contribution To Mbc Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial inherited component has been estimated to be present in 40-50% of PCA, and several genetic mutations have been implicated [4]. Among these, BRCA1 and BRCA2 mutations stand out for their renowned role in carcinogenesis in ovarian and female breast cancer, with recent evidence reporting mutated BRCA genes as a risk factor also for the development of male breast cancer [5]. BRCA genes are indeed tumour suppressor factors involved in DNA repair, in particular in the homologous recombination repair (HRR) process of double-strand breaks.…”
mentioning
confidence: 99%
“…The most frequent use of Next-Generation Sequencing (NGS) has identified an increasing number of genes suspected to be involved in cancer predisposition, especially for cancers with a familial component such as BC [32]. The current use of multigene panel testing for breast cancer predisposition has been a remarkable tool, although the genes included were based on female studies, limiting its use in male breast cancer [4] and creating a partiality in the genetic predisposition analysis.…”
Section: Discussionmentioning
confidence: 99%